The regional factor in economic development : (Organisation for Economic Co-operation and Development., 1961)
This report is divided into nine chapters. An outline of the factors that place some regions at a disadvantage to others in the same country and of the prncipal characteristics of the regional problems countered followed by chpters on the objectives and the concepts, respectively, of regional development. To problems of administrative organization, icluding the role of the various layers of government, the administrative, consultative and other bodies involved and the finalcial means aivailable for undertaking these polices.